2021
DOI: 10.3389/fonc.2021.651671
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adjuvant Chemoradiotherapy on Survival of Resected Pancreatic Adenocarcinoma Cancer: A Surveillance, Epidemiology and End Results (SEER) Analysis

Abstract: BackgroundThe benefits of postoperative adjuvant chemoradiotherapy (CRT) for pancreatic cancer remain controversial. The purpose of this study is to determine if adjuvant CRT can improve the overall survival of postoperative pancreatic cancer patients compared to adjuvant chemotherapy (CT).MethodsPatients with resected pancreas adenocarcinoma were identified in the Surveillance, Epidemiology, and End Results (SEER) database (2004–2016). Multivariate Cox regression was used to determine the factors related to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…On the other hand, in the retrospective analysis based on the SEER (Surveillance, Epidemiology and End Results) database, adjuvant CRT was associated with improved survival compared with adjuvant chemotherapy in particular subgroups of patients. The benefit was more significant in patients who were females (HR = 0.860; p = 0.005) and had pT3 (HR = 0.905; p = 0.04) and positive lymph nodes (HR = 0.88; p = 0.005) [30].…”
Section: Adjuvant Treatment (At)mentioning
confidence: 96%
“…On the other hand, in the retrospective analysis based on the SEER (Surveillance, Epidemiology and End Results) database, adjuvant CRT was associated with improved survival compared with adjuvant chemotherapy in particular subgroups of patients. The benefit was more significant in patients who were females (HR = 0.860; p = 0.005) and had pT3 (HR = 0.905; p = 0.04) and positive lymph nodes (HR = 0.88; p = 0.005) [30].…”
Section: Adjuvant Treatment (At)mentioning
confidence: 96%
“…In contrast, adjuvant chemoradiotherapy demonstrated improvement in OS compared to adjuvant chemotherapy (HR, 0.9; 95%CI, 0.881-0.977; p=0.004) in patients with resected pancreas adenocarcinoma based on a Surveillance, Epidemiology, and End Results (SEER) database analyses from 2004-2016. This benefit was more pronounced in females and patients with positive lymph node detected on surgical pathology ( 16 ).…”
Section: Timing Of Radiation Therapymentioning
confidence: 99%
“…On the other hand, the significance of adjuvant chemoradiotherapy (CRT) has not yet been established. The ESPAC-1 and EORTIC trial 40,891 showed no additional benefit of adjuvant CRT in patients with PDAC [ 18 ]; however, in one retrospective cohort study, some patients benefited more from adjuvant CRT than from adjuvant CT [ 19 ].…”
Section: Evidence Of the Benefits Of Adjuvant/neoadjuvant Chemotherap...mentioning
confidence: 99%